Autoimmune disease and COVID-19: a multicentre observational study in the United Kingdom. (4th April 2022) - Arachchillage, Deepa J; Rajakaruna, Indika; Pericleous, Charis; Nicolson, Philip L R; Makris, Mike; Laffan, Mike; ,
Abstract: Objective: To establish the demographic characteristics, laboratory findings and clinical outcomes in patients with autoimmune disease (AD) compared with a propensity-matched cohort of patients without AD admitted with COVID-19 to hospitals in the UK. Methods: This is a multicentre observational study across 26 NHS Trusts. Data were collected both retrospectively and prospectively using a predesigned standardized case record form. Adult patients (≥18 years) admitted between 1 April 2020 and 31 July 2020 were included. Results: Overall, 6288 patients were included to the study. Of these, 394 patients had AD prior to admission with COVID-19. Of 394 patients, 80 patients with SLE, RA or aPL syndrome were classified as severe rheumatologic AD. A higher proportion of those with AD had anaemia [240 (60.91%) vs 206 (52.28%), P  = 0.015], elevated LDH [150 (38.08%) vs 43 (10.92%), P  < 0.001] and raised creatinine [122 (30.96%) vs 86 (21.83%), P  = 0.01], respectively. A significantly higher proportion of patients with severe rheumatologic AD had elevated CRP [77 (96.25%) vs 70 (87.5%), P  = 0.044] and LDH [20 (25%) vs 6 (7.5%), P  = 0.021]. Patients with severe rheumatologic AD had significantly higher mortality [32/80 (40%)] compared with propensity matched cohort of patients without AD [20/80 (25%), P  = 0.043]. However, there was no difference in 180-day mortality between propensity-matched cohorts of patients with or without AD in general ( P  = 0.47). Conclusions: Patients with severe rheumatologic AD had significantly higher mortality. Anaemia, renal impairment and elevated LDH were more frequent in patients with any AD while elevated CRP and LDH were more frequent in patients with severe rheumatologic AD both of which have been shown to associate with increased mortality in patients with COVID-19.